USE OF PLASTIC BOTTLE MEDIA TO REDUCE MALADAPTIVE BEHAVIOR OF AUTIS CHILDREN (Single Subject Research in State Class II Elementary School 02 Serang City, Banten) - shellia sukma putri (Jurusan Pendidikan Luar Biasa, FKIP Universitas Sultan Ageng Tirtayasa, 2018)
Abstract The behavior of autistic children shows a striking presence compared to children in general. The difference in behavior of real autistic children is different related to the development of behavior of children his age. Based on the preliminary study that the researcher did in SKh. Negeri 02 Serang City, there are autistic children who have maladaptive behavior, namely getting out of the bench with quite a lot of frequency during the learning process so that it is considered disturbing by the class teacher and has attachment to certain objects, namely plastic bottles. Based on this, researchers are interested in using plastic bottles as learning media.This study aims to determine changes in the reduction of maladaptive behavior (out of the bench) that children often do with plastic bottles. The subjects in this study were a class II SDLB autistic student at SKh. Negeri 02 Serang City. The method in this study is a single subject research with A-B-A design. The collection technique is done by observation and documentation and analyzed by analysis in conditions and analysis between conditions. The results showed that the use of instructional media had a positive influence on the target behavior in children, seen from the average frequency in each session, namely phase A1 obtained an average of 12.5 points, phase B obtained an average of 5 points, phase A2 was obtained on average an average of 9.25 points. Based on the data obtained it is known that the use of plastic bottle media can reduce maladaptive behavior of autistic children in class II primary school in Skh. Negeri 02 Serang City